2016
DOI: 10.1007/s00592-016-0926-1
|View full text |Cite
|
Sign up to set email alerts
|

Levels of metabolic markers in drug-naive prediabetic and type 2 diabetic patients

Abstract: In the present study, patients with pre-DM and T2DM have higher serum levels of metabolic HGF, nesfatin, and betatrophin and lower levels of omentin, irisin, and OXT. Future longitudinal and interventional studies are required to confirm the utility of these markers as novel progression or therapeutic targets in the pharmacotherapy of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 38 publications
6
27
0
5
Order By: Relevance
“…In PCOS patients, circulating ZAG levels were reported to be consistently reduced [10,27,28]. However, the relationship between circulating betatrophin levels and PCOS is controversial and the studies in the literature are inconsistent [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Growing evidence indicates that these cytokines have some roles in the pathogenesis of T2DM and PCOS, and are also involved in IR development.…”
Section: Discussionmentioning
confidence: 99%
“…In PCOS patients, circulating ZAG levels were reported to be consistently reduced [10,27,28]. However, the relationship between circulating betatrophin levels and PCOS is controversial and the studies in the literature are inconsistent [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Growing evidence indicates that these cytokines have some roles in the pathogenesis of T2DM and PCOS, and are also involved in IR development.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a comprehensive meta-analysis by Li et al suggested that circulating betatrophin levels in T2D nonobese patients are higher than those in the nondiabetic control group [9]. Moreover, recent studies showed that plasma concentrations of metabolic markers, for example, betatrophin, as well as hepatocyte growth factor and nesfatin, are elevated in drugnaïve prediabetic and T2D patients in comparison to normoglycemic subjects [18,19]. It has also been observed that serum betatrophin concentration positively correlated with HbA1c and fasting plasma glucose in the group of patients with diabetes, prediabetic state, and metabolic syndrome [19] and with fasting plasma glucose and HOMA-IR in T2D and nondiabetic subjects [20].…”
Section: Introductionmentioning
confidence: 99%
“…The positive correlation of omentin-1 with HDL has been previously described in obesity, metabolic syndrome and cardiovascular disease. 30 However, the mechanism that explain these results was not clear. Most The mechanism for its elevation in obese patients was unclear but it was thought to be due to pro-inflammatory cytokines released from adipose tissue such as 1L-1 enhance intra-cellular zinc accumulation with intracellular copper efflux, and when released to blood it binds to ceruloplasmin.…”
Section: Discussionmentioning
confidence: 96%